Between the theory and method: the interpretation of the theory of Emilia Ferreiro for literacy - Fernanda Cargnin Gonçalves (Universidade Federal de Santa Catarina, 2008)
This article aims to show the difficulty of understanding the theory of Emilia Ferreiro by teachers from first grade at a school of public municipal city of Florianopolis / SC. It presents the theory of real Ferreiro described in his book "Psicogênese of Language Writing," co-authored with Teberosky, and interpretation of literacy observed in their practices of teaching. There are also options for work to teaching a child to escape the labeling of students in the literacy phases, which are based on essays, showing what is possible without turning theory into teaching method.